Exploring facets of the mindful personality: Dispositional mindfulness and the Big Five. (March 2021) - Haliwa, Ilana; Wilson, Jenna M.; Spears, Shantel K.; Strough, JoNell; Shook, Natalie J.
Abstract: Existing literature indicates inconsistencies regarding the pattern and strength of associations between mindfulness and the Big Five personality traits, potentially due to methodological differences across studies. To address this, we simultaneously assessed associations among mindfulness and all personality traits, controlled for demographic characteristics, and utilized multiple measures of mindfulness in an adult life-span sample ( N = 594). Mindfulness was consistently negatively associated with neuroticism. There were small to medium positive associations between mindfulness and conscientiousness, agreeableness, openness, and extraversion. Results differed modestly depending on the type of analysis (regression vs. bivariate correlations) and were mostly similar across different mindfulness measures. Major differences did not emerge as a function of demographic characteristics. Our findings advance the literature by addressing methodological limitations to demonstrate the importance of simultaneously assessing personality traits and using multidimensional measures of mindfulness.